Analysis of foundation sliding of an arch dam considering the hydromechanical behaviour - Braga Farinha, M. L. (2011)
This paper presents the application of a methodology which can be used to assess arch dam foundation stability, using the discrete element method (DEM) and the code 3DEC. A global three-dimensional model of a dam foundation was developed, in which some discontinuities were simulated and both the grout and drainage curtains were represented. The model, calibrated taking into account recorded data, was used to carry out non-linear mechanical analysis. The same model was employed to perform a hydraulic analysis, based on equivalent continuum concepts, which allowed the water pressure pattern within the foundation to be obtained. These water pressures were applied on discontinuities involved in the possible sliding mechanism along the dam/foundation interface, and the safety of the dam/foundation system was evaluated using a process of reduction of strength characteristics, with the aim of calculating the minimum safety factors that ensure stability. Results were compared with those obtained with the usual bi-linear uplift pressure distribution at the base of the dam, commonly used in concrete dam design. The relevance of carrying out hydraulic analysis in arch dam foundation failure studies is highlighted.